The passenger service improvement using fuzzy QFDbased on evidence reasoning approach; case study - Mirzazadeh, A (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2013)
The airline service quality is an important issue in the international air travel transportation industry. Thefirstpassengers' encounter with airline staff is at the airport and therefore, improving the quality of passenger services is one of the main objectives of airlines.The study applies an extension of the Quality Function Deployment to examine the performance of Iran Air in passenger service and propose suggestions for improvement.Human judgments are often vague, and it is not easy for passengers to express the weights of evaluation criteria and the satisfaction of airline service quality using an exact numerical value. Fuzzy logic is a methodology to deal with ill-defined nature of the customer's linguistic judgments required in the QFD.Also, the evidential reasoning based QFD is a methodology for synthesizing various types of assessment information provided by QFD team members. The presented model can be considers vagueness of human thinking style.The Intelligent Decision System (IDS) software has been used to solve the problem. The results have been demonstrated that the stafftrainingand the appropriate delayed flight handling are the most important elements of customer satisfaction and the highlighted areas for service improvement.